A review of structural, thermo-physical, acoustical, and environmental properties of wooden materials for building applications. (March 2017) - Asdrubali, F.; Ferracuti, B.; Lombardi, L.; Guattari, C.; Evangelisti, L.; Grazieschi, G.
Abstract: The current environmental and energetic crisis and the resulting regulations led to a new interest in using sustainable materials for building applications. Wood can be a material with high sustainable rates because it is recyclable, reusable and naturally renewable. Moreover, its excellent strength-to-weight ratios, thermal insulating and acoustical properties make it useful for different kinds of applications in buildings, ranging from structural beams and frames, insulating envelopes, windows, door frames, to wall and flooring materials and furniture. Although wood is commonly classified as a sustainable material, its real sustainability depends on different issues: appropriate forest management, manufacturing methods and site assembly, distance required for transportation and use of glues. Wood has also good seismic performances due to its lightweight and even if timber elements are not able to have a ductile behavior, using steel connection allows to build dissipative structure, as well platform frame and X-LAM panels systems. Insulation properties are related to low thermal conductivity values. Furthermore, wooden elements can be used to minimize sound transmission and they can be employed as sustainable materials as several Life Cycle Assessment studies demonstrate. This review paper aims to analyze the structural, thermal, acoustical and environmental properties of wooden materials for building applications; other properties such as fire resistance and durability were also taken into account. The work is completed by several tables and graphs with wood properties and by an updated and thorough reference list.